Escribiendo una defixio: los textos de maldición a través de sus soportes - Sánchez Natalías, Celia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The aim of this paper is to analyze binding curse tablets found in the Latin West from a material perspective, in order to rethink their multifaceted nature, since sometimes – but not always – defixiones are inscribed pieces of lead.